Swimming technique concepts: Technique similarities across the four competitive strokes - Havriluk, R. (Swimming World Magazine, 2020)
Although there are obvious differences in technique elements across all four competitive strokes, there are many similarities. Knowing about the similarities can help swimmers better understand specific movements and, consequently, make technique improvements more quickly. There are sinilarities in elbow flexion, elbow flexion to 90 degrees, head position (free, fly, and breast), arm entry (ree and back), push phase (free and fly) and difference exist e.g. in elbow flexion (fly and breast).